Effect of Changing Properties of Wythes in Precast Structural Sandwich Panels - Mohamed Abo El-Naga Kandil; Ahmed H. Abdelraheem; Mohamed Mahdy; Ahmed M. Tahwia (Civil Engineering Journal, 2020)
This study investigates the effects of changing in the properties of face and core wythes in structural sandwich panels (with dimensions of 500 500 mm and 120 mm total height). Concrete face wythes of three grades (80, 70, 37) MPa, thicknesses of (25, 35, and 45) mm, and three types of core materials (high density foam, polyethylene foam, and palm bark) were used in the production of panels. Steel shear connectors were installed in the panels with angle of 45º. Three-point bending load test was carried out on all panels and results were compared with both of the theoretical extremes capacities of non- composite and fully-composite states and ANSYS software results. The degree of composite action (%) and the (strength/weight) ratio were the main parameters that judged the specimens. It was found that upgrading concrete increased overall strength of slabs especially in high strength concrete (80 MPa), however the use of lightweight concrete (70 MPa) caused high (strength/weight) ratio due to very lightweight. Results revealed that decreasing thickness of concrete face wythes had a positive effect on strength/weight ratio (although the ultimate loads decreased) that enhanced the performance of panels as lightweight structural panels. The optimum face wythe thickness is that of 2.5 cm and has high (strength/weight) ratio. It was noticed that adding polyethylene foam as a core material results in positive effect and high (strength/weight) ratio. Results revealed that high strength concrete (80 MPa) and light-weight concrete (37 MPa) are very successful in the production face wythes of precast light-weight sandwich panels that can obtain high (strength/weight) ratio and high percent of composite action.